Fostering Nationalism among University Students in Indonesia: A Communal Perspective - Endang Purwaningsih; Blackson Kanukisya (Society)
This study’s primary aim is to investigate globalization’s impact on nationalism in Indonesia, specifically focusing on the youth population. The research seeks to understand how globalization influences nationalist sentiments, particularly in the context of the Indonesian educational system. The chosen methodology centers around implementing a Civic Education learning model, aiming to activate and enhance nationalism values among students. The research employs a structured approach, utilizing a test on nationalism knowledge administered before and after implementing the Civic Education learning model. This method allows for a comprehensive assessment of the potential impact of the learning model on students’ understanding of nationalism. The analysis involves measuring the mean score difference between pre-test and post-tests, employing statistical calculations such as mean difference, the standard deviation of the difference, the standard error of the mean difference, and calculated t-values. Additionally, behavioral-scale tests are conducted to evaluate the mean score difference in students’ nationalism behavior. Quantitative calculations and analyses are employed to substantiate the research hypothesis. The statistical findings indicate a significant influence of the Civic Education learning model on students’ knowledge of nationalism and behavior. The mean score differences before and after the model’s implementation and the calculated t-values provide robust evidence of the positive impact on students’ nationalist sentiments. The study extends its contribution to pedagogy by demonstrating the efficacy of alternative teaching methods, specifically in Civic Education. The findings suggest that implementing the Civic Education learning model enhances practical application and holds promise in strengthening Indonesia’s global influence. The research aligns with established concepts of nationalism, emphasizing the actualization of patriotism through the collective development of clear national goals and objectives. The study aims to contribute meaningful insights to the ongoing discourse on nationalism in Indonesia, particularly among the youth.